Thermal and electrochemical reduction of zinc ferrite doped with polymer - Ivanova, N.M.; Muldakhmetov, Z.; Vissurkhanova, Y.A.; Soboleva, E.A.; Beisenbekova, M.E. (Electrochemistry Communications, 2021)
Zinc ferrite samples were prepared by a co-precipitation method in the presence and absence of a polymer stabilizer (polyvinyl alcohol), followed by heat treatment at 500, 700, and 900 ◦C. The structural phase and morphological features of these samples were studied by X-ray phase analysis and electron microscopy. It was found that polymer-doped zinc ferrite undergoes thermal reduction by the decomposition products of the polymer, and is also capable of further electrochemical reduction on a Cu cathode in an aqueous alkaline solution. Zinc ferrite reduction products (ZnO, Fe0) exhibit electrocatalytic activity for the electrohydrogenation of p-nitroaniline.
Keywords: Zinc (II) ferrite; Polyvinyl alcohol; Thermal and electrochemical reduction; Electrocatalytic activity